2019
DOI: 10.1103/physrevd.99.065016
|View full text |Cite
|
Sign up to set email alerts
|

Circular orbit of a test particle and phase transition of a black hole

Abstract: The radius of the circular orbit for the time-like or light-like test particle in a background of general spherically symmetric spacetime is viewed as a characterized quantity for the thermodynamic phase transition of the corresponding black hole. We generally show that the phase transition information of a black hole can be reflected by its surrounding particle's circular orbit. *

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Moreover, it was also found that the temperature and pressure corresponding to the extremal points of the radius and minimal impact parameter are highly consistent with the thermodynamic metastable curve for the Kerr-AdS black holes. This study was also generalized to other black hole backgrounds [36][37][38]. For example, in Ref.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, it was also found that the temperature and pressure corresponding to the extremal points of the radius and minimal impact parameter are highly consistent with the thermodynamic metastable curve for the Kerr-AdS black holes. This study was also generalized to other black hole backgrounds [36][37][38]. For example, in Ref.…”
Section: Introductionmentioning
confidence: 93%
“…[37] the authors studied the relation between the thermodynamic phase transition and the circular orbit for charged test particles. Photon orbits and thermodynamic phase transition were examined in Gauss-Bonnet AdS black holes [36], massive black holes [37], and even in a general spherically symmetric spacetime [38]. In addition, the presence of photon orbit also reveals a York-Hawking-Page type phase transition of spacetimes [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, some endeavours are trying to replace the role of event horizon with the photon orbit around the black hole. Based on the case studies in [38,39], it was found that the circular orbit radius of the photon can be a characteristic quantity to reflect the thermodynamic phase structure of a spherically symmetric black hole [40]. Related extensions can also be seen in [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…What's more, the observation of black hole opens a new window for its thermodynamic research. As a strong gravitational system, the trajectory of the photon moving around the black hole has been proved to be an effective tool to reflect its phase structure [45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%